Meningkatkan Kemampuan Pemahaman Matematis Siswa SMK Menggunakan Pendekatan Kontekstual Pada Materi SPLTV - Mentari Dini; Nuraeni Nuraeni; Ika Wahyu Anita (Universitas Sarjanawiyata Tamansiswa, 2018)
This study aims to examine and analyze about contextual approach to improve understanding ability in senior high school Bakti Utama. The population in this research is XI grade senior high school in Bandung Barat. This study was designed qualitative descriptive method. Based on the results and discussion students understanding ability had improved.